Study on Productive Performances, Constraints, and Opportunities of Improved Chicken under Village Production System in West Shewa Zone, Ethiopia - Amanuel Bekuma; Abdissa Tadesse (Advances in Agriculture)
The study was conducted to determine productive performances, constraints, and opportunities of Bovans Brown (BB), Sasso, and crossbred chickens under village production system in Gindeberet district of West Shewa, Ethiopia. A total of 139 randomly selected smallholder chicken producers were involved in the study from six purposefully selected peasant associations (PAs) from the district. Information was gathered on average egg production/year, age at the first egg laying, constraints, and opportunities of improved chicken production during the study. The data collected were analyzed using Statistical Package for Social Science (SPSS) version 24, and Z-test was employed to test the difference among agro-ecologies on a certain variable. The mean annual eggs produced by BB (189.34 ± 0.99 eggs/hen/year) and by Sasso (180.82 ± 0.9 eggs/hen/year) were higher than those of crossbred chicken (111.26 ± 0.77 eggs/hen/year). Moreover, a significant difference (p<0.05) was observed for crossbred and exotic chickens' egg production performances between agro-ecological zones. The mean age at the first egg laying (182.28 ± 1.61 days) of crossbred chickens was higher than the mean age at the first egg laying (164.29 ± 0.41 days) of exotic chickens. Also, the mean age at the first egg laying of improved chicken breeds was statistically significant (p < 0.05) between agro-ecological zones. Prevalence of disease, inadequate veterinary services, predators, and shortage of balanced concentrate mixture feeds were among the constraints hindering improved chicken production in the study area. However, high demand of chicken and chicken products, participation of NGOs in dissemination of improved chicken, presence of government policy, and availability of manpower were the major potentials encouraging chicken production in the study area. Therefore, practical poultry production training and extension should get primary emphasis to combat the existing constraints. Therefore, good poultry management practices should be promoted to improve chicken productivity in the study area.